A biomimetic magnetically recoverable palladium nanocatalyst for the Suzuki cross-coupling reaction. Issue 52 (12th May 2016) - Dubey, Abhishek V.; Kumar, A. Vijay
Abstract : A mussel-inspired magnetically recoverable and reusable Pd nanoparticles based catalyst was developed for Suzuki–Miyaura cross-coupling reaction with a wide range of substrate scope in a benign solvent system. Abstract : Mussel-inspired magnetically recoverable and reusable Pd nanoparticles immobilised on polydopamine-coated nano-Fe3 O4 were prepared and characterized by techniques such as TEM, SEM, XPS, XRD, FT-IR and DSC-TGA. The catalyst demonstrated remarkable activity for Suzuki–Miyaura cross-coupling reactions of aryl halides and aryldiazonium salts with arylboronic acids in a benign solvent system. A wide range of substrates were converted, including the challenging relatively poorly reactive aryl bromides. The yields of the products were good to excellent. Moreover, the protocol has several advantages such as tolerance of sensitive functional groups, magnetic recovery and reusability of the catalyst up to five cycles. Mechanistic studies showed that the palladium nanoparticles followed a dissolution and redeposition pathway during the catalytic cycle. The developed methodology was successfully utilized for the synthesis of a precursor of the sartan drugs.